What should armies do? armed forces and civil security - Clarke, John L. (John Louie) 1952- (Routledge, 2016)
This volume focuses on two key elements in the North American and European security debate: the decline of both the external threats to most North American and European states, and that of budgetary resources available for defense. These twin declines are coupled with a desire on the part of civil leaders to engage the military in more domestic tasks and the desire of senior military leaders to preserve force structure, resulting in a dynamic in which civil leaders will ask their militaries to do more, and military leaders will be more inclined to say yes. As such, this book focuses on the enormous increase in the provision of non-military services and support asked of North American and European military establishments.